Pengaruh Kepribadian Individu Dan Pendidikan Kewirausahaan Terhadap Motivasi Berwirausaha (Studi Pada Mahasiswa Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2020) - Kusumawardani, Nabilla Anjali; Djaelani, Abdul Kodir; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the influence of individual personality and entrepreneurship education on the entrepreneurial motivation of Management students at the Faculty of Economics and Business, Islamic University of Malang class of 2020. The research method used is quantitative research methods. Sampling was carried out on Management students from the Faculty of Economics and Business, Islamic University of Malang class of 2020 using the Slovin formula so that the sample obtained in this study was 81 respondents who were taken using a purposive sampling technique with criteria determined by the researcher. To obtain data, this research used a data collection method with a questionnaire. The data analysis used is instrument testing, normality testing, classical assumptions, multiple linear regression analysis, hypothesis testing, and coefficient of determination using the SPSS application. The results of this research show that individual personality and entrepreneurship education simultaneously have a significant positive effect on the entrepreneurial motivation of Management students at the Faculty of Economics and Business, Islamic University of Malang class of 2020. Furthermore, individual personality and entrepreneurship education partially have a significant positive effect on the entrepreneurial motivation of Management students at the Faculty of Economics and Business. Islamic University of Malang class of 2020. Keywords: Individual personality, entrepreneurship education, entrepreneurship motivation